Foundations of Civil Liability for the Violation of Privacy in Cyberspace in Imamiyyah Jurisprudence and Iranian Law - Ebrahimi Ramandi, Jamshid; Afsharnia, Tayeb; Yaqoti, Ebrahim (Legal Studies in Digital Age, 2024)
Privacy, as one of the fundamental rights of individuals, is protected both in legal systems and in Islamic jurisprudence. Violation of this right may lead to civil liability, the foundations of which can be examined within jurisprudence and law. In the jurisprudential system, principles such as the rule of no harm (qāʿidat lā ḍarar), the principle of respect for the believer’s privacy, the principle of respect for human dignity, the principle of correctness (aṣālat al-ṣiḥḥa), the principle of generality of permission (ʿumūm al-idhn), and the rule of causation (qāʿidat al-tasabbub) emphasize the necessity of observing privacy and compensating for damages resulting from its violation. These rules demonstrate that any unauthorized intrusion into individuals’ private space is prohibited in jurisprudential terms and entails liability. In the legal system, three main theories have been proposed to explain civil liability arising from the violation of privacy. The fault-based liability theory considers the establishment of liability contingent upon proving the fault of the offending party. The risk-based liability theory deems the mere occurrence of damage sufficient to establish liability without the need to prove fault. Finally, the theory of right-guarantee treats privacy as a fundamental right and regards its violation, without the need to prove fault or risk, as sufficient grounds for civil liability. The examination of these foundations, based on a descriptive and analytical research method, shows that in both Islamic jurisprudence and positive law, the violation of privacy is deemed unacceptable, and necessary safeguards for compensating damages have been foreseen. This reflects the significance of protecting this fundamental right and the necessity of adopting effective legal and religious measures to prevent its violation and to compensate for the resulting harm.